Comparative Study on The Performance of Automotive Industry Companies on Tax Incentive Policies in Indonesia, Thailand, and Malaysia - Arvin, Vincentius; Putra, Hariyati (International Environmental Conferrence on Biosustainability Advancement, 2024)
The purpose of this study was to examine the comparison of the performance of automotive companies before and after the implementation of Tax Incentive policies in Indonesia, Thailand and Malaysia. Measurement of Company Performance was measured by the ratio of profitability and stock prices. Profitability ratios were measured using Return on Assets (ROA) and Net Profit Margin (NPM), while stock prices were measured using Earning Per Share (EPS). The population used in this study were Indonesian, Thai and Malaysian automotive industry companies listed on the stock exchanges of each country during 2018 – 2021. This study used a saturated sampling technique with a total sample of 33 companies with total of 396 data. The data analysis method used in this study was one-way anova analysis using SPSS 26 software’s. The results of this study indicate that Malaysia is the most effective country in implementing Tax Incentive policies as indicated by the most stable company performance among the three countries, but it can be underlined that there is only a significant difference in the NPM Ratio as a variable indicator between company performance among the three countries.